Allele-Specific Reduction of the Mutant Huntingtin Allele Using Transcription Activator-Like Effectors in Human Huntington's Disease Fibroblasts. Issue 4 (April 2016) - Fink, Kyle D.; Deng, Peter; Gutierrez, Josh; Anderson, Joseph S.; Torrest, Audrey; Komarla, Anvita; Kalomoiris, Stefanos; Cary, Whitney; Anderson, Johnathon D.; Gruenloh, William; Duffy, Alexandra; Tempkin, Teresa; et al.
Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by an abnormal expansion of CAG repeats. Although pathogenesis has been attributed to this polyglutamine expansion, the underlying mechanisms through which the huntingtin protein functions have yet to be elucidated. It has been suggested that postnatal reduction of mutant huntingtin through protein interference or conditional gene knockout could prove to be an effective therapy for patients suffering from HD. For allele-specific targeting, transcription activator-like effectors (TALE) were designed to target single-nucleotide polymorphisms (SNP) in the mutant allele and packaged into a vector backbone containing KRAB to promote transcriptional repression of the disease-associated allele. Additional TALEs were packaged into a vector backbone containing heterodimeric Fok I and were designed to be used as nucleases (TALEN) to cause a CAG-collapse in the mutant allele. Human HD fibroblasts were treated with each TALE-SNP or TALEN. Allele-expression was measured using a SNP-genotyping assay and mutant protein aggregation was quantified with Western blots for anti-ubiquitin. The TALE-SNP and TALEN significantly reduced mutant allele expression ( p < 0.05) when compared to control transfections while not affecting expression of the nondisease allele. This study demonstrates the potential of allele-specific gene modification using TALE proteins, and provides a foundation for targeted treatment for individuals suffering from Huntington's or other genetically linked diseases.